Cytomegalovirus Infection of Human Teratocarcinoma Cells in Culture - Gonczol, E; Andrews, P. W; Plotkin, S. A (Journal of general virology, 1985)
The Wistar Institute of Anatomy and Biology, 36th Street at Spruce, Philadelphia, Pennsylvania 19104, U.S.A. Whereas human cytomegalovirus (HCMV) did not replicate in human embryonal carcinoma (EC) cells, it did replicate in some of the differentiated cells arising following the exposure of TERA-2-derived human EC cells to retinoic acid. On the other hand, retinoic acid did not induce a permissive state in several other diverse human cell lines, including an EC line, 2102Ep, which did not differentiate in response to this agent. Also, both TERA-2 and 2102Ep EC cells differentiated to a limited extent when grown at low cell density and a few of these cells became permissive for HCMV. Thus, susceptibility is the result of differentiation and not due to a direct effect of retinoic acid on viral replication. The nature of the block to HCMV replication in human EC cells is unknown, but viral DNA could be detected in the nucleus within an hour of infection and there was an increased anchorage-independent growth of undifferentiated and differentiated cells following HCMV infection. Viral replication is not subject to a general block in these cells, since another herpesvirus, herpes simplex virus type 1, replicated well. Keywords: cytomegalovirus, human teratocarcinoma, differentiation, teratogenic effect Received 30 July 1984; accepted 14 November 1984.